2015
DOI: 10.1155/2015/209418
|View full text |Cite
|
Sign up to set email alerts
|

Midline Cervical Cleft: Review of an Uncommon Entity

Abstract: Introduction. Midline cervical cleft is a rare congenital malformation which nonetheless has a classic presentation. This study presents one of the largest single series of new patients with MCC and provides an exhaustive review and catalogue of publications from the international literature. Materials and Methods. Retrospective chart review performed in two academic medical centers and literature review performed with primary verification of all quoted references. Results. Ten patients with MCC were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 69 publications
1
42
0
1
Order By: Relevance
“…The lesion is situated in the midline between the chin and suprasternal area, with variable length and width. Puscas [14] found a positive correlation between the size of the defect and the patient's age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lesion is situated in the midline between the chin and suprasternal area, with variable length and width. Puscas [14] found a positive correlation between the size of the defect and the patient's age.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that there is a predominance of CMCC in the Caucasian population, mainly in females, with a F:M ratio of 2:1 [15, 16]. However, Achard et al in 2016 [17] found an equal ratio between males and females with CMCC, and Puscas [14] even found a male predominance, with 8 boys and 2 girls, in his published retrospective series in 2015. Consistent with most studies, we identified 13 females and 8 males with a CMCC (a ratio of 1.6:1), with most of them being Caucasian (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although the location may be similar, thyroglossal duct cysts present as subcutaneous cystic neck masses without overlying skin change, readily distinguishing this entity from MANICs . In contrast, midline cervical clefts have evident overlying skin changes with a distinctive linear patch of atrophic skin with a skin tag at the superior aspect . Bronchogenic cysts can also occur in the suprasternal notch region, although these are slightly more inferiorly located .…”
Section: Discussionmentioning
confidence: 99%
“…Our patient's lesion resembled a congenital midline cleft. Congenital midline clefts are characterized by a superior skin tag with an inferior blind sinus .…”
Section: Discussionmentioning
confidence: 99%